2017
DOI: 10.1111/jnu.12311
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Resilience of Burn Patients in South Korea

Abstract: In the nursing practice, nurses need to pay attention to the burn patient's self-esteem and family support. Concrete interventions and strategies to improve the resilience of burn patients are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 22 publications
1
15
0
6
Order By: Relevance
“…Concurrent validity showed high correlations of RS with life satisfaction, morale, and depression (Wagnild & Young, 1993). This scale is widely used internationally (Bhamani, Pasha, Karmaliani, Asad, & Azam, 2015;Coelhoso, Garcia Del Castillo, Marzo, Dias, & Castillo-Lopez, 2017;Jang et al, 2017; Navarro-Abal, Lopez-Lopez, & Climent-Rodriguez, 2018) and has been translated into Taiwanese for use in trajectories of regenerating family resilience in 54 adolescents with cancer, the Cronbach's alpha was .947 (Chen, 2013). In this study, we used the Taiwanese version with the participants, and the Cronbach's alpha was .928.…”
Section: Instrumentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Concurrent validity showed high correlations of RS with life satisfaction, morale, and depression (Wagnild & Young, 1993). This scale is widely used internationally (Bhamani, Pasha, Karmaliani, Asad, & Azam, 2015;Coelhoso, Garcia Del Castillo, Marzo, Dias, & Castillo-Lopez, 2017;Jang et al, 2017; Navarro-Abal, Lopez-Lopez, & Climent-Rodriguez, 2018) and has been translated into Taiwanese for use in trajectories of regenerating family resilience in 54 adolescents with cancer, the Cronbach's alpha was .947 (Chen, 2013). In this study, we used the Taiwanese version with the participants, and the Cronbach's alpha was .928.…”
Section: Instrumentsmentioning
confidence: 99%
“…Previous studies have found that patients with good resilience can effectively increase their adaptability and quality of life (Kool, Geenen, Egberts, Wanders, & Van Loey, 2017). Many factors may affect resilience, such as gender, subjective well-being, self-concept, self-esteem, and family resources (He, Cao, Feng, Guan, & Peng, 2013;Jang, Park, Chong, & Sok, 2017;Khanlou & Wray, 2014;Masood, Masud, & Mazahir, 2016;Wu, Chang, Tsai, & Liang, 2018). There are many studies on resilience, but these have mainly been focused on chronic disease patients such as dialysis (Freire de Medeiros et al, 2017), Parkinson's disease (Robottom et al, 2012), cancer (Wu et al, 2018;Wu, Liu, Li, & Li, 2016), and major trauma (Teche et al, 2017), as well as on caregivers (Inci & Temel, 2016;Palacio, Krikorian, & Limonero, 2018;Saria et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Twenty‐two quantitative and 10 qualitative studies were included. Four focused on pediatric burn survivors (Duke et al, 2018; Maskell, Newcombe, Martin, & Kimble, 2013; Sveen, Sjöberg, & Öster, 2014; Willebrand et al, 2011); 25 studies focused on adults (Abrams, Ogletree, Ratnapradipa, & Neumeister, 2016; Bayuo, Agbenorku, & Amankwa , 2016; Christiaens et al, 2015; Elsherbiny, Salem, El‐Sabbagh, Elhadidy, & Eldeen, 2011; Goyatá & Rossi, 2009; Hunter et al, 2013; Idrees, Faize, & Akhtar, 2017; Jang, Park, Chong, & Sok, 2017; Johnson, Taggart, & Gullick, 2016; Juozapavicien, Rimdlka, & Karbonskiene, 2012; Kornhaber, Wilson, Abu‐Qamar, & McLean, 2014; Liang, Wang, Yao, Pan, & Wang, 2012; Martin, Byrnes, McGarry, Rea, & Wood, 2017; Mashreky et al, 2008; Ohrtman et al, 2018; Park, Choi, Jang, & Oh, 2008; Pfitzer et al, 2016; Shahid, Ismail, & Khan, 2018; Sproul, Malloy, & Abriam‐Yago, 2009; Titscher, Lumenta, Kamolz, Mittlboeck, & Frey, 2010; Wasiak et al, 2014; Wiechman et al, 2018; Yuxiang et al, 2012; Zamanzadeh, Valizadeh, Lotfi, Salehi, & Khalili, 2016; Zhang et al, 2014); and three studies focused on both adults and children with burns (Ahuja, Mulay, & Ahuja, 2016; Simons, Price, Kimble, & Tyack, 2016; Vetrichevvel et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Some studies also focused on 2 years (Christiaens et al, 2015; Martin et al, 2017; Wiechman et al, 2018), 8 years (Kornhaber et al, 2014), and 9 years post‐burn (Sveen et al, 2014). Others did not specify the exact post‐discharge follow‐up period (Bayuo et al, 2016; Jang et al, 2017; Liang et al, 2012; Park et al, 2008; Pfitzer et al, 2016; Willebrand et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation